Experimental Study on the Icing of Rotating Intake Cones in Wind Tunnels Under Supercooled Large-Droplet Conditions - Zhiqiang Zhang; Huanyu Zhao; Dongyu Zhu; Hao Dai; Zhengzhi Wang (Aerospace)
Supercooled droplets that collide with the windward surface of the aircraft will freeze, which results in icing on both stationary and rotating components. The ice accretion on rotating surfaces is physically different from those on stationary components. The icing phenomenon on the surface of a rotating intake cone was investigated in an icing wind tunnel, and the influence of icing conditions of supercooled large droplets on the experimental results was analyzed. In the experiments, the ice accretion of the intake cone was studied under various conditions, including rotational speed, wind speed, icing temperature, droplet diameter, and icing time. The ice shape on the surface of the intake cone is notably unique due to the influence of centrifugal force, which produces a longer feather-like ice structure that has a significant effect on the performance of the engine. The process of ice shedding caused by centrifugal force is also critical for the engine anti-icing process. Therefore, it is essential to study the icing characteristics under rotational effects during the design and verification process of engine anti-icing systems.